Study the efficiency of pheromone traps with virgin female on attracting male of Chrysomya megacephala( Diptera: Calliphoridae) - Al-jamali, Nassir A.; Al-Sudani, Ali A.H. (Journal of Kerbala for Agricultural Sciences, 2018)
Chrysomya megacephala secondary myiasis fly is one of insects that has medical and veterinary importance in the world which caused secondary myiasis to stinking decomposing animal wounds , in order to study the efficiency of pheromone traps with virgin females to attract it,s male,it is important to determine the factors affecting the efficacy of pheromone traps when they are used to monitor and control C. megacephala fly. This study was conducted at Frehaa region, 4 km North-east of Karbala city . The results showed the best number of virgin females were (5)which gave 0.76 insect/trap/day Compared with 0.42 and 0.33 insect/trap/day at traps which provided 1.0 and 10.0 virgin female Respectively. The best hight to hang trap was 1.5 m with 1.27 insect/trap/day Compared with 0.55 and 0.61 insect/trap/ day the traps which at hight 0.5 and 1.0 m respectively while the best distance between pheromone traps was 50 m to prevent the interaction between traps which gave 0.77 insect/trap/day compared with 0.38 , 0.27 insect/trap/day in distances 100 , 150 respectively .the result showed that the activating attracting period were 4 days, must be replaced with anther virgin females with 2 days old to complete it,s sexual maturity in order to be able to attract it,s males.